Stress analysis of acacia mangium furniture by computer aided design and engineering analysis / Mohd Ariff Jamaludin, Mansur Ahmad and Kamarulzaman Nordin - Jamaludin, Mohd Ariff; Ahmad, Mansur; Nordin, Kamarulzaman (2006)
A finite element analysis of a simple design chair was carried out in this study. A vertical static load was applied at the centre point of the seal and another horizontal static load was applied on the centre point of the backrest simultaneously. Three sets of load of 900N (90kg) and 380N (38kg) , 1800N (180kg) and 760N (76kg); and 3600N (360kg) and 1520N (152kg) were applied on the seat and on the backrest respectively. The maximum stresses for these three different load levels were 5.9173N/mm2 , 11. 8346N/mm2 and 23.6698 N/mm2 respectively. The load versus stress relationship indicated that the yield stress was proportional to the applied load. At higher load level the yield stress on the modelled chair was also higher. Stress concentration occurred at the end joints; at the centre of the backrest and the seat, and the mid span of the front and back seat rails. Stress located nearer to the end joint had higher stress values than the stress located away from the end joint. The chair fulfilled the performance criteria in BS 4875(1985) and BS 5873 (1980, 1991) for the chair size mark 4 and 5 under normal and severe rating. The modelled chair did not fail even when the applied load had been increased to twice of the load requirements in the BS 4875(1985) and BS 5873 (1980. 1991) tests standard.